Air quality and health benefits of China's emission control policies on coal-fired power plants during 2005-2020 - Wu, Ruili; Liu, Fei; Tong, Dan; Zheng, Yixuan; Lei, Yu; Hong, Chaopeng; Li, Meng; Liu, Jun; Zheng, Bo; Bo, Yu; Chen, Xiaoting; Li, Xin; et al. (Environmental research letters, 2019)
Coal-fired power plants (CPPs) dominate China's energy supply systems. Over the past two decades, the explosive growth of CPPs has led to negative air quality and health impacts in China, and a series of control policies have been implemented to alleviate those impacts. In this work, by combining a CPPs emission database over China (CPED), a regional chemical transport model (WRF-CMAQ), and the integrated exposure-response model, we summarized historical and ongoing emission control policies on CPPs over China, investigated the air quality and health impacts of China's CPPs during 2005-2020, and quantified the benefits of each policy. We found that despite the 97.4% growth of coal-fired power generation during 2005-2015, PM2.5 exposures caused by emissions from China's CPPs decreased from 9.0 g m−3 in 2005 to 3.6 g m−3 in 2015. The active emission control policies have decreased CPPs-induced PM2.5 exposures by 10.0 g m−3 during 2005-2015. We estimated that upgrading end-of-pipe control facilities and early retirement of small and low-efficiency units could respectively reduce PM2.5 exposures by 7.9 and 2.1 g m−3 during 2005-2015 and avoid 111 900 and 31 400 annual premature deaths. Since 2015, China's government has further required all CPPs to comply with the so-called 'ultra-low emission standards' before 2020 as a major component of China's clean air actions. If the policy is fully deployed, CPPs-induced PM2.5 exposures could further decrease by 2.5 g m−3 and avoid 43 500 premature deaths annually. Our study confirms the effectiveness of tailored control policies for China's CPPs and reveals that those policies have played important roles in air quality improvement in China.